ANALYSIS OF THE IMPLICATIONS OF USTADZ ABDUL SOMAD'S YOUTUBE CONTENT LECTURES ON THE UNDERSTANDING OF "WE WILL BE HAPPY IF WE MAINTAIN PRAYERS" IN MARENU VILLAGE, AEK NABARA BARUMUN DISTRICT - Hasibuan, Etti Handayani; Khatibah (International Journal of Cultural and Social Science, 2025)
The purpose of this study was to analyze the implications of Ustadz Abdul Somad's YouTube content lecture "We Will Be Happy If We Maintain Prayer" in Marenu Village, Aek Nabara Barumun District. The main purpose of this study is to describe how digital preaching lectures can have an impact on people's lives to understand, absorb, and practice Islamic teachings through prayer. This study uses a qualitative method with a Phenomenological approach to understand the experiences of informants related to the implications of Ustadz Abdul Somad's YouTube content lecture. Data collection techniques were carried out through interviews, observations, and documentation. Research informants consisted of ustadz, community leaders, village heads, and local people. Data were analyzed through the process of data reduction, data presentation, and drawing conclusions. The validity of the data is strengthened through triangulation and member check. The results of this study provide a good impression of the lives of the people in Marenu Village, Ustadz Abdul Somad's lecture was able to raise public awareness of the importance of maintaining prayer as a primary obligation that brings inner peace and true happiness where there is an increase in the quality of community worship. Residents who were previously negligent in praying began to show changes by being more diligent in carrying it out and the mosque that was previously quiet is now crowded and the weekly religious studies are routinely carried out by both mothers and teenagers. therefore the lecture has succeeded in providing a deep understanding to the people of Marenu Village, because of its simple, interesting and meaningful interaction style so that the community experiences positive changes in their lives with the emergence of mutual cooperation carried out in the mosque, the habit of reprimanding each other in goodness, and increasing concern for religious education.